PENGETAHUAN DAN SIKAP PERAWAT TENTANG NYERI PASIEN PASCA BEDAH DI RUANG PERAWATAN BEDAH RUMAH SAKIT UMUM DAERAH TORA BELO KABUPATEN SIGI - Jumain; Silva (Sekolah Tinggi Ilmu Kesehatan Indonesia Jaya Palu, 2020)
Surgery is a treatment that uses an invasive method by opening the part of the body to be treated. A preliminary study conducted by researchers on December 10, 2019 on 5 nurses in the surgical treatment room of the Tora Belo Hospital, Sigi Regency, 3 nurses said that pain in surgical patients was part of the wound process due to trauma experienced. Another nurse said that surgical patients can be given painkillers. The results of interviews with surgical patients that nurses only give anti-pain medications recommended by doctors. The purpose of this study was to determine the knowledge and attitudes of nurses about the management of postoperative pain in the surgical treatment room of the Tora Belo Regional General Hospital, Sigii Regency. This type of research is descriptive research. The variables in this study were nurses' knowledge and attitudes about postoperative pain. This research was conducted in the surgical treatment room of the Tora Belo Regional General Hospital, Sigi Regency. The data used are primary data and secondary data. Data analysis using univariate analysis. The population in this study amounted to 16 people and the sampling method with the total population. The results of the univariate analysis of respondents with good knowledge of 75%, respondents with sufficient knowledge of 25%. Respondents behaved well 62.6%, moderate attitude 31.2%, attitude less 6.2%. The conclusion in this study was that most of the respondents had good knowledge and attitudes of nurses about post-surgical patient pain in the surgical treatment room of the Tora Belo Regional General Hospital, Sigi Regency. It is recommended that nurses in the surgical treatment room of the Tora Belo Regional General Hospital, Sigi Regency increase their knowledge and attitudes in handling postoperative pain